FUNCTIONAL MEANING IN LINGUISTICS (Modern education and development, 2025)
this article explores the concept of functional meaning in linguistics, focusing on its connection with parts of speech and grammatical categorization. Functional meaning is considered an integral component of a word’s semantic structure, which helps determine its syntactic role within a sentence. The study examines both traditional and modern linguistic approaches to this notion, including structural, generative, and cognitive perspectives. Emphasis is placed on the dynamic and context-dependent nature of functional meaning, as well as its role in language teaching and computational analysis.